Performa Solar Water Heater Collector Dengan Menggunakan Reflektor Dan Variasi Laju Aliran Air - Masykur, Masykur; Saputra, Maidi; Jayadi, Farid; Munawir, Al; Supardi, Joli; Muazar, Muazar (universitas teuku umar, 2022)
This study aims to look at the performance of the solar water heater collector with the addition of a reflector. Reflector is used to increase the absorption of solar radiation. The test was carried out by varying the water flow rate in the pipe, namely 75 l/hour, 150 l/hour and 225 l/hour with a collector tilt angle of 30°. Tests are carried out every one hour, starting at 09.00-16.00 WIB for each variation. Parameters measured in this study included glass temperature, inlet water temperature, outlet water temperature, pipe temperature, absorber temperature, ambient temperature and wind speed. The results showed that the highest efficiency occurred at a flow rate of 225 l/hour, which was 62.44% at IT 3,366 MJ/m2, and the highest ratio of outlet water temperature and inlet water temperature was 1.51 at a flow rate of 75l/h. Adding a reflector to the coverslip can increase collector efficiency.